2019
DOI: 10.1021/acsbiomaterials.9b01286
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Cornea: Cell Laden Hydrogel Incorporated Decellularized Matrix

Abstract: The decellularization protocols applied on the corneal stromal constructs in the literature usually fail to provide a corneal matrix with sufficient mechanical and optical properties since they alter the extracellular matrix (ECM) microstructure. In this study, to overcome these limitations, a hybrid cornea stromal construct was engineered by combining gelatin methacrylate (GelMA) and decellularized ECM. Photo-cross-linking of impregnated cell laden GelMA in situ using different UV cross-linking energies (3200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 50 publications
0
19
0
Order By: Relevance
“…The decellularization cornea applied in cornea stroma engineering can not mimic the environment of extracellular matrix well because it changes the original ECM micro-environment during the decellularization process. In order to solve this problem Uyanıklar et al [133] fabricate a novel scaffold which is a combination of GelMA and decellularized matrix. They reported that this material has better compressive modulus (5040 and 870 kPa) and light transmittance value (53.6%), due to the special structure of GelMA makes up for the inherent shortcomings of the decellularization matrix.…”
Section: Gelma For Cornea Stroma and Other Tissue Engineeringmentioning
confidence: 99%
“…The decellularization cornea applied in cornea stroma engineering can not mimic the environment of extracellular matrix well because it changes the original ECM micro-environment during the decellularization process. In order to solve this problem Uyanıklar et al [133] fabricate a novel scaffold which is a combination of GelMA and decellularized matrix. They reported that this material has better compressive modulus (5040 and 870 kPa) and light transmittance value (53.6%), due to the special structure of GelMA makes up for the inherent shortcomings of the decellularization matrix.…”
Section: Gelma For Cornea Stroma and Other Tissue Engineeringmentioning
confidence: 99%
“…A cell laden hybrid hydrogel made from GelMA incorporated with decellularized bovine cornea matrix showed an increased light transmittance value (around ten‐fold increase), compressive modulus (around six‐fold increase) and degradation profile close to native cornea compared with decellularized bovine cornea matrix. [ 76 ] In addition, modification of agarose hydrogels with fish‐derived gelatine exhibited >96% transmittance of visible light, tensile strength and young's modulus of 49–60 and 525–596 MPa, respectively, with enhanced corneal endothelial cells (CECs) long‐term viability (⩾4 weeks) and attachment compared with agarose hydrogels alone and modified with GRGD, lysine and poly lysine. [ 77 ] Kong and colleagues [ 78 ] used electrospinning technique to improve the biomechanical and biological properties of gelatine‐based hydrogels with highest biomimetics activity on limbal stromal stem cells differentiation toward keratocytes or fibroblasts, phenotype maintenance, and in vivo tissue regeneration of the defected cornea in rabbit model.…”
Section: Hydrogels For Corneal Tissue Engineering and Cells/drug Deliverymentioning
confidence: 99%
“…2019 [76] Agarose-gelatine hydrogels Rabbit CECs Attachment and viability over 4 weeks. Over 96% transmittance of visible light.…”
Section: Bovine Cornea Keratocytesmentioning
confidence: 99%
“…An alternative to helical type I collagen with secondary structure is the use of gelatin or methacrylated gelatin (GelMA) [ 12 , 56 , 67 , 68 , 69 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]. Gelatin, a denatured and hydrolyzed form of collagen, and its methacrylated form, have demonstrated broad applicability across many tissue engineering applications due biocompatibility, tailorable mechanical properties, low cost, ease of processing, and transparency [ 76 , 78 ], making them an attractive biomaterial for ocular applications.…”
Section: Engineering a Cornea Mimetic: Mechanical Properties And Biomaterials Structurementioning
confidence: 99%
“…Studies use many corneal stromal cell sources for investigating cell-material interactions in stromal tissue engineering strategies, including human CKs, bovine CKs, human CSCs, human LSSCs, and rat LSSCs [ 31 , 70 , 71 , 72 , 75 , 92 , 94 , 107 ]. The use of biomarkers to identify stromal cells include keratocan, lumican, α-actinin, aldehyde dehydrogenase 1 family, member A1 (ALDH1A1), and aldehyde dehydrogenase 3 family, member A1 (ALDH3A1).…”
Section: Engineering a Cornea Mimetic: Cell Types And Their Functionmentioning
confidence: 99%